Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 11 - Section 11.2 - Arithmetic Sequences - Exercise Set - Page 839: 31


$a_n=-\frac{1}{3} + \frac{1}{3}(n-1)$; $a_{20} = 6$

Work Step by Step

RECALL: (1) The $n^{th}$ term, $a_n$, of an arithmetic sequence can be found using the formula: $a_n=a_1 + d(n-1)$ where $a_1$ = first term $n$ = term number $d$ = common difference (2) The common difference $d$ can be determined using the formula $d= a_n-a_{n-1}$ where $a_n$ = $n^{th}$ term $a_{n-1}$ = term before $a_n$ The given arithmetic sequence has $a_1=-\frac{1}{3}$ and $d=\frac{1}{3}$. Substitute these values into the formula in (1) above to obtain the arithmetic sequence's formula for the general term: $a_n=-\frac{1}{3}+(\frac{1}{3})(n-1)$ Solve for the 20th term for the sequence using the formula above to obtain: $a_{20} = -\frac{1}{3} + \frac{1}{3}(20-1) \\a_{20} = -\frac{1}{3}+\frac{1}{3}(19) \\a_{20} = -\frac{1}{3}+\frac{19}{3} \\a_{20} = \frac{18}{3} \\a+{20} = 6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.